Implementation of Business Model Canvas in Micro, Small, and Medium Eenterprises (MSME) Wall Panel Furniture as an Effort to Increase Production to Expand Market Share (Universitas Negeri Semarang, 2021)
Abstract. The panel furniture business is one of Indonesia's quite widely practiced industries. This makes panel furniture business activists have to innovate to create good business models and create panel furniture with high aesthetic value and good business processes in business continuity that can compete with MSMEs throughout Indonesia. This study aims to support the sustainability of business processes by implementing the Business Model Canvas. Data collection methods used in this study were interviews and observation. From the research that has been done, it is found that the implementation of the Business Model Canvas makes business processes run better than before. This is because the business processes that occur run more regularly.